What can bodies do? Bodies and caves in the Karst Neolithic - Dimitrij Mlekuž (Documenta Praehistorica, 2011)
This paper discuses ways in which bodies – human and animal – were produced in the Neolithic of the Karst. Bodies are seen as cumulative processes shaped by forces of encounters with the material world, rather than as biological givens. Thus, the paper focuses on the process of embodiment mediated with other bodies and landscape, especially important places such as caves. It explores the unique ways in which caves affect bodies, and how these affected bodies created new societies. In the Neolithic Karst, everyday contacts and interactions between humans, animals, the landscape and caves and rock shelters profoundly changed all the participants. A new hybrid society emerged, consisting of human and non-human bodies.